The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/jso.23800
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of lobectomy, segmentectomy, and wedge resection for stage I non‐small cell lung cancer

Abstract: This study suggested that tumor size or age alone should not be the criteria to encourage sublobar resection. For stage I NSCLC, survival following segmentectomy was inferior to lobectomy. Patients undergoing intentional sublobectomy achieved comparable survival as those who received lobectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 46 publications
4
65
2
2
Order By: Relevance
“…Mortality was also higher in the limited resection group, but did not reach statistical significance (7,8). The study is more than 20 years old, but a recent meta-analysis has confirmed that lobectomy is still better than limited resection for stage IA ≤2 cm tumours (9). This also has been observed in a recent population-based study comprising 15,760 patients with T1aN0M0 non-small cell lung cancers (10,493 or 66% adenocarcinomas) from the Surveillance, Epidemiology and End Results database who underwent lobectomy, segmentectomy or wedge resection.…”
mentioning
confidence: 80%
“…Mortality was also higher in the limited resection group, but did not reach statistical significance (7,8). The study is more than 20 years old, but a recent meta-analysis has confirmed that lobectomy is still better than limited resection for stage IA ≤2 cm tumours (9). This also has been observed in a recent population-based study comprising 15,760 patients with T1aN0M0 non-small cell lung cancers (10,493 or 66% adenocarcinomas) from the Surveillance, Epidemiology and End Results database who underwent lobectomy, segmentectomy or wedge resection.…”
mentioning
confidence: 80%
“…In individuals with severe disease and resectable lung cancer, there is evidence that newer surgical treatments (sublobar resection or lung volume reduction surgery [LVRS]) and ablative therapies (stereotactic radiosurgery or radiofrequency ablation) are valid alternatives to consider due to their acceptable risk and good long-term outcomes [48][49][50][51][52][53] . There are even reports of successful lung cancer surgical treatments in patients that previously underwent endobronchial LVRS for severe emphysema 54 .…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…For tumors less than 2 cm, segmentectomy was equivalent to lobectomy. Recently, Zhang et al [20] reported a meta-analysis of sublobectomy (segmentectomy and wedge resection) vs. lobectomy. They selected 53 studies from the PubMed and EMBASE databases and showed that the indication for sublobar resection due to tumor size (less than 2 cm) or age alone would not be sufficient.…”
Section: Meta-analysismentioning
confidence: 99%